2014
DOI: 10.1128/jvi.01509-14
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Capsid-Associated Tegument Components in Kaposi's Sarcoma-Associated Herpesvirus

Abstract: Capsid-associated tegument proteins have been identified in alpha-and betaherpesviruses to play an essential role in viral DNA packaging. Whether and how such tegument proteins exist in gammaherpesviruses have been mysteries. Here, we report a 6-Å-resolution cryo-electron microscopy (cryo-EM) structure of Kaposi's sarcoma-associated herpesvirus (KSHV) virion, a member of the oncogenic gammaherpesvirus subfamily. The KSHV virion structure reveals, for the first time, how capsid-associated tegument proteins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 53 publications
6
78
1
Order By: Relevance
“…ORF25, which makes up the capsomere, has three domains: the floor, middle, and upper domains (35). Binding of the inner tegument protein(s) to the capsid is mediated by the upper domain of the major capsid proteins and the triplex protein(s) (1,35,36). We previously showed that capsid formation is not affected in the absence of ORF33, and ORF33 is an inner tegument protein of mature MHV-68 virions (8).…”
Section: Discussionmentioning
confidence: 99%
“…ORF25, which makes up the capsomere, has three domains: the floor, middle, and upper domains (35). Binding of the inner tegument protein(s) to the capsid is mediated by the upper domain of the major capsid proteins and the triplex protein(s) (1,35,36). We previously showed that capsid formation is not affected in the absence of ORF33, and ORF33 is an inner tegument protein of mature MHV-68 virions (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although pUL77-mGFP and pUL93 could still interact when capsid formation was abrogated-for instance, upon disruption of the MCP ORF-proper nuclear localization of pUL77 seems to depend on additional factors. Whether pUL77 and pUL93 interact directly, as reported for the corresponding proteins of alpha-and gammaherpesviruses (23,24,75), remains to be tested by expressing the proteins independent of viral infection. Interestingly, in the accompanying article by P. Köppen-Rung and colleagues (84), direct interaction of pUL77 and pUL93 was confirmed by using such an approach, and the domain mediating the binding to UL93 was mapped to the N terminus of pUL77.…”
Section: Discussionmentioning
confidence: 99%
“…1D), indicating that they expressed an amount of RTA sufficient for lytic reactivation. It is important to note that the 3= end of the ORF31 coding sequence overlaps the 5= end of ORF32, a gene encoding a capsid-associated tegument protein that is homologous to members of the UL17 family of genes (23). UL17 of herpes simplex virus 1 (HSV-1) is essential for DNA packaging into the capsid and, thus, infectious virus production (24).…”
mentioning
confidence: 99%